Blended Learning Approach through Industry Electives. (July 2014) - Reddy K., Sudheer; Chatarajupalli, Srinagesh; Singh, Anoop; Manisha,; Prasad T.V., Bhanu
One of the strategic functions of the Infosys Education & Research Unit is the 'Industry-Academia partnership program'—Campus Connect (CC), launched in May 2004 to nurture an ecosystem to enhance the right quality and quantity of the input talent (students in the engineering institutes) before they join. A systemic change in the education system is implemented through CC by co-creation and co-teaching of Industry Electives along with Autonomous Engineering Institutions and Deemed Universities in India. The purpose of industry elective is to provide customized programmes for students in institutions that are based on 'learn and apply', enable students to have special interest to round-up their general education and facilitate faculty members to create learning channels with industry. The CC has developed a framework for effective, consistent and predictable deployment of the industry electives so that the talent available for the Information Technology (IT) industry is industry ready and available in large quantities. This model was further strengthened by incorporating co-teaching for the co-created industry electives. This article focuses on how co-creation and co-teaching of industry electives successfully blend the sessions offered by Infosys experts through the technology-based virtual learning mode with the lectures offered by the institution faculty members, live in their respective classes.